BUSSINESS ENTERPRISES AND HUMAN RIGHTS STANDARDS - Geethani Jeewanthi, M.K. (University of Jaffna, 2017)
Globalization and other developments of the world have directed business corporations to play an increasingly vital role at both international and national levels. The number of businesses increase day by day and, consequently this has led policy makers to consider whether these business corporations have any kind of adverse effects on stake holders. Neglecting other human rights is one such unfavorable concern which would be caused by a business and this research paper intends to discuss about this issue. The main objective of this research paper is to identify the recognized human rights principles that have to be followed by business cooperations in their daily activities. This research would look for available international conventions, guidelines, principles, policies and available domestic materials which govern this research area. From the theoretical aspect the author has used the human rights based approach for this study and the doctrinal qualitative research method as its main methodology. In conclusion, notes that there is a challenge of balancing economic growth and human rights protection at all levels. While appreciating the efforts taken at global level for providing responsibility for business enterprises to protect human rights, it is also noted that there are lacunas to be addressed further.
Keywords: business enterprises; human rights; guiding principles